2007
DOI: 10.1080/01612840600997990
|View full text |Cite
|
Sign up to set email alerts
|

College Students' Perspective on Smoking Cessation: “If the Message Doesn't Speak to Me, I Don't Hear It”

Abstract: The purpose of this study was to document the smoking cessation experiences of three groups of 18-24-year-old college students and explore their ideas for cessation. Focus group interviews were conducted with former smokers (n = 7), smokers struggling to quit (n = 7), and smokers with no desire to quit (n = 5). Participants indicated a need for smoking cessation programs that would help the students understand the immediate physiological impact of smoking, addictive nature of nicotine, and benefits of using ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…The proportion of smokers or e-cigarette users in our study who used pharmacotherapy to quit smoking or vaping was lower compared to the general EU population. Among students, the price of pharmacotherapy used to quit smoking is often a barrier and may result in low usage of NRT and other medications in this group of smokers [38]. National tobacco control strategies should consider access to free-of-charge pharmaceuticals to quit smoking as an element of smoking cessation programs.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of smokers or e-cigarette users in our study who used pharmacotherapy to quit smoking or vaping was lower compared to the general EU population. Among students, the price of pharmacotherapy used to quit smoking is often a barrier and may result in low usage of NRT and other medications in this group of smokers [38]. National tobacco control strategies should consider access to free-of-charge pharmaceuticals to quit smoking as an element of smoking cessation programs.…”
Section: Discussionmentioning
confidence: 99%
“…The KAP model, if effective, would be expected to lead to reduced smoking rates among adolescents. Staten and Ridner [33] have reported that inappropriate messaging may be less effective if no targeting is used.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, young adults frequently do not self-identify as Bsmokers,â nd thus may not tune-in to cessation messages or believe that evidence-based cessation programs fit them (Y. Choi et al 2011;Guillory et al 2016;Staten and Ridner 2007). As a result, young adults have not been the target of prevention, and there have been limited efforts targeting them for cessation.…”
Section: Prevescalation As a Research Gap And An Intervention Opportumentioning
confidence: 99%